The Mitigation of Covid-19 in the Spiritual, Psychosocial, Physical Aspects and Anxiety Disorders of Health Workers in Hospital : Mitigation of Covid-19 in the Spiritual, Psychosocial, Physical Aspects and Anxiety Disorders of Health Workers in Hospital - Inna Sholicha; Aida Ratna Wijayanti (University of Muhammadiyah Malang, 2021)
Introduction: The entire world is experiencing the COVID-19 crisis at this time. Hospitals must determine steps to keep treating COVID-19 patients while still provide optimal service by minimizing the risk of COVID-19 transmission. Health workers feel tremendous pressure because of their work. Managing mental and psychosocial health is as essential as maintaining physical care for frontline health workers. Objectives: The Research aimed to identify the mitigation of COVID-19 from the spiritual, psychosocial, and physical aspects and its effects on anxiety disorder in health workers in health services. Methods: The research type was analytic observational and cross-sectional design with cluster random sampling technique using dichotomy multivariate regression analysis, The research instrument used by google form is submitted through the whats app questionnaire DASS 21. The respondents were 99 health workers at Muhammadiyah Hospital and Aisyiyah Hospital Ponorogo. Results: The results show that 70.8% did not have an anxiety disorder, 22.1% had mild anxiety, 6.1% had moderate anxiety, and 1% had severe anxiety. 47% of health workers applied spiritual mitigation well, 84.9% had good psychosocial comfort, and 51.1% had good physical relief. There was an effect of mitigation of COVID-19 in the spiritual, psychosocial, and physical aspects of health workers in dealing with Anxiety Disorder in the New Normal Era in the Health Service. Conclusions: Covid-19 can affect health service procedures and the quality of health for health workers. This condition is one of the efforts to ensure the safety of health workers by paying attention to spiritual, psychosocial, and physical aspects; in this case, the management of hospital human resources in dealing with a pandemic is excellent so that it has a positive impact on anxiety disorder incidents for health workers in the hospital environment.